How safe is it to manage diverticular colovesical fistulation non‐operatively?. (27th March 2013) - Radwan, R.; Saeed, Z. M.; Phull, J. S.; Williams, G. L.; Carter, A. C.; Stephenson, B. M.
Abstract: Aim  Colovesical fistula (CVF) is an uncommon condition. Diagnosis and management varies according to presentation and aetiology. The identification of patients suitable for conservative management and their outcome following this approach has not been well documented. Methods  The clinical outcomes of all patients diagnosed with a CVF over a 7‐year period from an uro‐radiological database were reviewed. Cases secondary to diverticular disease were analysed with respect to the approach by which they were managed: those treated surgically and those managed conservatively. Results  Sixty‐two patients (32 men) were diagnosed with CVF of whom 53 (85%) had diverticular disease. Twenty‐seven (mean age 69 years, range 42–90) underwent surgery (with a stoma in 59%) with a 30‐day mortality of 15%. Those managed conservatively ( n  =   26) were older (mean age 76 years, range 39–87) and frailer (62% American Society of Anesthesiologists Grades III and IV). At 1 and 3 years following diagnosis there was no difference in mortality between these two groups and only one death was as a consequence of urosepsis. Conclusion  Many patients with CVF secondary to diverticular disease can be safely managed non‐operatively.